BANK XIZMATLARI SAMARADORLIGINI OSHIRISHDA RAQAMLI BANK XIZMATLARINING O’RNI VA BUNDA XORIJIY MAMLAKATLAR TAJRIBASI - Xaydarov Sardor Xamdamjon o’g’li (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
This scientific article provides a comprehensive analysis of enhancing the efficiency of banking services through the development of digital banking services, the current level of their implementation, and the use of foreign best practices to further improve banking service efficiency. In particular, existing digital banking services in developed countries such as the USA, the United Kingdom, and India were examined and analyzed. Additionally, the study explored the population’s level of utilization of banking services, especially digital services, which are considered a key factor in the development of banking services, and general proposals and recommendations were formulated.